Evidence of Oath in Case Dispute over General Election Results in Indonesia - Sumali, Sumali; Esfandiari, Fitria; Fauzia, Ana (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
In practice law proof according to laws, roles the judge's conviction had limited in a way normative with element “at least two tools evidence”. As a result, when there is one applicant in case dispute results in election general (PHPU) which turned out to be only presenting information witness as tool proof, then matter the no can process because no sufficient condition as in applicable regulations. The writing article aims to examine: 1) the authority of the Court Constitution (MK) in adjudicating PHPU; 2) the domination of PHPU cases at the Constitutional Court; 3) the aspect constitutionality of PHPU; 4) proof and tools proof in PHPU; and 5) urgency tool proof swear. The method used in this research is normative legal research using statutory and conceptual approaches. The results of the research show that the PHPU examination by the Constitutional Court is not just a matter of calculators or quantitative numbers, but also concerns the qualitative issue of holding elections based on honesty and fairness. Therefore, the use of sworn evidence in the PHPU dispute resolution process has quite objective relevance and urgency, namely: First, because there is a possibility that the Petitioner will have difficulty or minimally present sufficient evidence, due to the relatively short time duration in the PHPU settlement; Second, the PHPU case is not a case with a purely legal dimension, but rather a political problem behind which the disputing parties at the Constitutional Court stand thousands or even millions of constituents who emotionally need honesty and justice.